Spatial and seasonal variability of horizontal temperature fronts in the Mozambique Channel for both epipelagic and mesopelagic realms - Sudre, Floriane; Dewitte, Boris; Mazoyer, Camille; Garçon, Véronique; Sudre, Joel; Penven, Pierrick; Rossi, Vincent (Frontiers in Marine Science, 2023)
Ocean fronts are moving ephemeral biological hotspots forming at the interface of cooler and warmer waters. In the open ocean, this is where marine organisms, ranging from plankton to mesopelagic fish up to megafauna, gather and where most fishing activities concentrate. Fronts are critical ecosystems so that understanding their spatio-temporal variability is essential not only for conservation goals but also to ensure sustainable fisheries. Frontal activity is thus an integrated indicator of the health status of oligotrophic oceanic systems. The Mozambique Channel (MC) is an ideal laboratory to study ocean front variability due to its energetic flow at sub-to-mesoscales, its high biodiversity and the currently debated conservation initiatives. Meanwhile, fronts detection relying solely on remotely-sensed Sea Surface Temperature (SST) cannot access aspects of the subsurface frontal activity that may be relevant for understanding ecosystem dynamics. In this study, we used the Belkin and O’Reilly Algorithm on remotely-sensed SST and hindcasts of a high-resolution nested ocean model to investigate the spatial and seasonal variability of temperature fronts at different depths in the MC. We find that the seasonally varying spatial patterns of frontal activity can be interpreted as resulting from main features of the mean circulation in the MZ region. In particular, horizontally, temperature fronts are intense and frequent along continental shelves, in islands’ wakes, at the edge of eddies, and in the pathways of both North-East Madagascar Current (NEMC) and South-East Madagascar Current (SEMC). In austral summer, thermal fronts in the MC are mainly associated with the Angoche upwelling and seasonal variability of the Mozambique current. In austral winter, thermal fronts in the MC are more intense when the NEMC and the Seychelles-Chagos and South Madagascar upwelling cells intensify. Vertically, the intensity of temperature fronts peaks in the vicinity of the mean thermocline. Considering the marked seasonality of frontal activity evidenced here and the dynamical connections of the MC circulation with equatorial variability, our study calls for addressing longer timescales of variability to investigate how ocean ecosystem/front interactions will evolve with climate change.